2022
DOI: 10.3390/molecules27020426
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Thermal Properties of Composites Prepared from Pistachio Shell Particles Treated Chemically and Polypropylene

Abstract: The purpose of the present work was to prepare polypropylene (PP) matrix composited filled with chemically treated pistachio shell particles (PTx), and evaluate their effect on the composites’ thermal properties. PP-PTx composites were formulated in different PTx content (from 2 to 10 phr) in a mixing chamber, using the melt-mixing process. The PTx were chemically treated using a NaOH solution and infrared spectroscopy (FTIR). According to thermogravimetric analysis (TGA), the treatment of pistachio shell part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 40 publications
4
8
0
Order By: Relevance
“…Beg et al [ 74 ] reported a 3.3% increase of X c with 40 wt% of wood flour in PP. Similar observations were made in the literature [ 73 , 74 , 75 , 76 , 77 ].…”
Section: Resultssupporting
confidence: 90%
“…Beg et al [ 74 ] reported a 3.3% increase of X c with 40 wt% of wood flour in PP. Similar observations were made in the literature [ 73 , 74 , 75 , 76 , 77 ].…”
Section: Resultssupporting
confidence: 90%
“…This is a result of the steric effect, with PCL being hydrophobic and BP being hydrophilic, leading to good dispersion in the fabrication of composites [ 46 , 79 ]. Similar observations were reported for the other types of WPCs [ 73 , 80 , 81 ].…”
Section: Resultssupporting
confidence: 89%
“…Salazar-Cruz et al [ 39 ] obtained similar results. In fact, by adding filler content, they obtained an increase in the composite’s melting temperature and ΔHm, indicating that a larger number of crystalline zones were present.…”
Section: Resultssupporting
confidence: 56%